Female Sex Workers: From Health Perspectives to an Integrative Intervention Model Crimes against commercial Sex workers: - Ramanathan1, Vanisree (International Journal of Psychosocial Rehabilitation, 2020)
Female sex workers are always the target of the HIV/AIDS government intervention program and disease control. But they are exploited by multiple stakeholders, living in stigma, discrimination, illhealth and abuse. An understanding of the sexual and reproductive health status of the female sex-workers and an assessment of effectiveness of the community mobilisation program for the emancipation of the female sex workers are essential to bring positive policy change. Even though multiple government programs are available for the welfare of this community and civil society organisations are working closely to give awareness and assisting to implement government programs, the living conditions of the female sex workers are reported to the worse. By using both quantitative and qualitative research methods, this research work unveil the living realities of the female sex workers in Pune city from their perspectives. Instead of being engaged as part of the solution to the HIV/AIDS pandemic, sex workers are treated as part of the problem. The research shows that Sex work is segmented between the enclosed and street segments, marked by main differences in working conditions, risk of victimization, and self-esteem. FSWs in street sectors are always discriminated and labelled as criminals by the hostile society, due to their low levels of education, and become vulnerable to the violence by criminals and the police force-with obvious consequences for the health and well-being of sex workers The existing laws are criminalising and victimising the sex workers without initiatives for prevention, changing their living conditions and protection of their rights. Instead of compulsory detention, this research suggests an evidence-based, voluntary, community empowerment services and integrative intervention strategies.